STRATEGI PEMBELAJARAN HADIS UNTUK MENUMBUHKAN KARAKTER DISIPLIN SISWA DI SEKOLAH MENENGAH ATAS - Hotimah, Husnul; Saputri, Marsanda; Muhammad Raihan Akbar; Farhan; Yusria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Hadith learning plays a strategic role in Islamic Religious Education as a means of instilling values ​​and developing the disciplined character of high school students. This study aims to examine the hadith learning strategies recommended in the literature and their role in fostering students' disciplined character. The method used was library research, analyzing scientific journals, books, and relevant sources. The results of the study indicate that contextually and applicably designed hadith learning can foster students' disciplined character by instilling the values ​​of responsibility, punctuality, trustworthiness, and order. Strategies that have been influential in fostering student discipline include Project-Based Learning, collaborative learning, reflective learning, the use of interactive digital media, and the living hadith approach. The successful implementation of these strategies is supported by infrastructure, support from educators and parents, while obstacles include limited media, learning motivation, Quranic literacy, and teachers' technological competence